THE CONCENTRATIONS OF ITRACONAZOLE AND HYDROXYITRACONAZOLE AFTER ORAL DRUG APPLICATION IN HEALTHY SUBJECTS: THE INFLUENCE OF GENDER - Stanojković, Tijana; Miljković, Milijana; Rančić, Nemanja; Kovačević, Aleksandra; Dragojević Simić, Viktorija (Halo 194 Scientific Journal of Emergency Medicine, 2021)
The aim of our study was to investigate the influence of gender on itraconazole and hydroxyitraconazole plasma concentrations in healty humans after oral application of itraconazole in one dose. Pharmacokinetic analysis was performed after oral administration of itraconazole in a single dose of 100 mg in 22 male and 16 female healthy volunteers. Blood samples were taken before drug administration, as well as at appropriate time intervals up to 72 hours thereafter. Itraconazole and hydroxyitraconazole concentrations were determined using a validated liquid chromatography method with mass spectrometric detection (LC-MS/MS), while their pharmacokinetic parameters were calculated by using Kinetica programme, version 5.0: Cmax,Tmax,PIK (0-72), PIK(0-∞),T1/2, and Ke.The median values of both itraconazole and hydroxyitraconazole were lower in women in comparison to men during the whole observed period. Moreover, median values ​​of Cmax, PIK(0-72) and PIK(0-∞) parameters were also significantly lower in women, concerning both itraconazole (p=0.005, 0.036 and 0.036, respectively) and its metabolite (p=0.004, 0.010 and 0.044, respectively). Elimination parameters - T1/2 and Ke did not differ between genders.Women were less exposed to the itraconazole and its active metabolite than men after its oral administration, possibly as a result of less bioavailability of the drug, including more intense presystemic metabolism due to higher expression and/or activity of enzyme isoform which metabolises itraconazole, needed to be confirmed by pharmacogenomic analyzes.
Keywords: itraconazole; hydroxy-hydroxyitraconazole; plasma concentrations; healthy subjects; gender